PP-48 Population pharmacokinetics and dosing optimisation of cefathiamidine in infants and children. Issue 10 (20th September 2017) - Zhao,
Abstract : Background: Cefathiamidine, a first-generation cepha-losporin, was approved by the China Food and Drug Ad-ministration for the treatment of adults and children with infections due to susceptible bacteria. As the paediatric pharmacokinetic data is limited, our aim was to evaluate the population pharmacokinetics of cefathiamidine in infants and children and define the appropriate dose in order to optimise cefathiamidine treatment. Methods: Blood samples were collected from infants and children treated with cefathiamidine and concentra-tions were quantified by HPLC-MS. Population pharmaco-kinetic analysis was performed using NONMEM software. Results: Seventy-four children (age range: 0.35–11.81 years) were included. Spars pharmacokinetic samples (n=172) were available for analysis. A one-compartment model with first-order elimination showed the best fit with the data. A covariate analysis identified that body-weight had a significant impact on cefathiamidine phar-macokinetics. Monte Carlo simulation demonstrated that the current recommended dose of 100 mg/kg/dayBID resulted in only 51.5% of simulated infants with age <2 years and 61.8% of children with age ≥2 years achieving the target 70% fT>MIC against Streptococcus pneumonia (MIC 0.25 mg/litre). Conclusion: The population pharmacokinetics of cefa-thiamidine was evaluated in infants and children and an optimal dosing regimen was established based on sim-ulation.